2003
DOI: 10.1021/jp0221439
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Absorption Studies of n-Heptane under High Pressure

Abstract: Mid-infrared spectra of neat n-heptane at room temperature are presented over a pressure range from ambient to 70 kbar. The application of hydrostatic pressure induces frequency shifts, band splittings, and significant changes in the line shapes of internal vibrational modes both in liquid and in solid phases. The results are discussed in terms of the liquid-solid phase transition and changes of the population of molecular conformers. Evidence for a solid-solid phase transition near 30 kbar is also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
43
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 28 publications
8
43
0
1
Order By: Relevance
“…High‐pressure Raman scattering studies at ambient temperature were performed on n ‐heptane, which remained stable over the entire range of pressures. A liquid‐solid transition occurred at a pressure of approximately 1.5 GPa ,,. At 7.5 GPa, changes in the Raman modes and the spectra were interpreted as the solid‐solid transition …”
Section: Experimental Studies Of Individual Hydrocarbon Transformationsmentioning
confidence: 99%
“…High‐pressure Raman scattering studies at ambient temperature were performed on n ‐heptane, which remained stable over the entire range of pressures. A liquid‐solid transition occurred at a pressure of approximately 1.5 GPa ,,. At 7.5 GPa, changes in the Raman modes and the spectra were interpreted as the solid‐solid transition …”
Section: Experimental Studies Of Individual Hydrocarbon Transformationsmentioning
confidence: 99%
“…Figure 6a shows the intensity ratio of I 1130 /I 1090, which is a representation of the population of trans and gauche conformers. [23][24][25][26][27][28] The I 1130 /I 1090 intensity ratio increases with increase in pressure suggesting an increase in TT (all-trans) population. These modes cease to exist beyond 12.3 GPa because of a possible phase transition.…”
Section: Methyl Rocking Regionmentioning
confidence: 99%
“…Infrared absorption experiments performed over a pressure range from ambient to 7 GPa revealed that n -heptane undergoes a liquid to solid transition at 11.8–14.9 GPa and a possible solid–solid transition at near 3 GPa. 10 Since then, molecular dynamic simulation calculations of n -heptane have confirmed the existence of the liquid–solid transition at 1.2–1.5 GPa. 11 Recent Raman spectroscopic investigations carried out up to a pressure of 16 GPa have indicated that a liquid–solid and a solid–solid phase transition happen at around 1.5 GPa and 7.5 GPa, respectively.…”
Section: Introductionmentioning
confidence: 98%